PEMBUBARAN ORMAS “RADIKAL” DALAM PERSEPEKTIF PERUNDANG-UNDANGAN (Kajian Khusus Perppu No. 02 Tahun 2017) - Imam Mahdi (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2017)
The Government Regulation on Law Enforcement (Perppu), has the same  legal force as the law, but is tem- porary because it must  obtain approval by the Parliament. Exit of Perppu No. 2 Year 2017 on Amendment to Law no. 17Year 2003 on Public  Organization. The legal basis  of the President to issue  the Perppu is stipulated in Article 22 of the1945 Constitution of the Republic of Indonesia, essentially the Perppu is issued because of the urgency of the matter, meaning that  if not issued by the Perppu, the government can not take legal action for the interest of the State. In fact, this Perppu is used to dissolve community organizations, especially Hizbur Tahrir Indonesia (HTI) which is considered by the government to deviate from Pancasila ideology and endanger the integrity of NKRI. As a result, there are pros and cons against Perppu No. 2 Year 2017. .